The Effect Of A Period Rhythmic Aerobic Exercise With Ginger Consumption On Serum Levels Of TNF-Α, IL-6 And Insulin Resistance In Obese Middle-Aged Women With Diabetes Mellitus - M Asadi; E Banitalebi; Z Esfadir; M Ghafari (Armaghane Danesh Bimonthly Journal, 2017)
ABSTRACT   Background & aim: Diabetes is a metabolic disorder associated with neuropathy, renal diseases, peripheral vascular disease, atherosclerosis, high blood pressure and inflammation. The use of supplements, herbal extracts, and exercise training for the treatment of diseases and metabolic disorders is common among people. The aim of this study was to investigate the effect effect of a period rhythmic aerobic exercise with ginger consumption on serum levels of TNF-α, IL-6 and Insulin resistance in obese middle-aged women with diabetes mellitus   Methods: In the present study, 46 obese diabetic women (BMI > 30, blood fasting sugar more than 150-250 mg/dL, 45-60 years old) were selected and randomly assigned into four groups including:  ginger (n=12), aerobic exercise training + ginger (n=12), aerobic exercise training (n=12) and control (n=10). Participants in supplementary groups received four 250 mg capsules ginger extract 1000 mg daily for 10 weeks. Aerobic training program included 10 weeks of training, 3 sessions per week and each session was 60 minutes at 55% maximum heart rate during the first week and gradually increased with the progress of the training program to 75 percent of maximum heart rate. Each session consists of warm up (10 minutes), the main part of the training involves performing aerobic exercises in a standing position (40 minutes) and recovery in sitting (10 minutes).   Results: No significant difference between four groups at level of TNF-α and IL6 was seen, but a significant degrease was observed between pre-test and post-test in (Training + ginger) group at levels of TNF-α (p=0.028), IL-6 (p=0.012), insulin resistance (p=0.009), insulin (p=0.007) and fasting serum glucose (p=0.000),   Conclusion: According to obtained results, it appeared that aerobic training plus ginger extract consumption had better effect on serum inflammatory factors in obsess women with diabetes              type 2.